Financial tactics and terms for the sophisticated international investor - Schultz, Harry D. (New York : Harper & Row, 1974)
The book provides several things that were missing in the realm of money investing. There have been an incredible number of changes in the investment world in recent years. It provides the techniques that have grown around these changes, things like Eurodollars, what are they and how you use them
ucj 14/01/2019
Loans
Keywords: Investments; International finance